Intravascular platelet activity correction by fosinopril in arterial hypertension patients with metabolic syndrome - I. N. Medvedev; V. V. Tolmachev (Российский кардиологический журнал)
The aim of the study was to assess therapeutic effects offosinopril on intravascular platelet (PL) activity inpatients with arterial hypertension (AH) and metabolic syndrome (MS). Thirty-three patients received fosinopril (10 mg/d) for 4 months. Dynamics of anthropometry and lipid profile parameters, plasma and PL lipid peroxidation, blood and PL anti-oxidant activity, intravascular PL activity were assessed. Ln AH and MS patients, fosinopril improved peroxidation syndrome and intravascular PL activity. Long-term fosinopril treatment could strengthen this beneficial effect. To reduce body mass in AH and MS patients, fosinopril should be combined with non-pharmaceutical interventions.